PENILAIAN KINERJA PORTOFOLIO BERDASARKAN KALKULASI IMBAL HASIL DENGAN METODE TIME WEIGHTED RETURN (TWR) DAN DOLLAR WEIGHTED RETURN (DWR) PADA KELOMPOK INDEKS TEMATIK - Suryawati, Baiq Nurul; Abidin, Zainal; Muttaqillah, Muttaqillah (Distribusi - Journal of Management and Business, 2022)
This study aims to assess portfolio performance using two methods, namely the time weighted return method and the dollar weighted return method. The portfolio is formed on the BUMN 20 index which shows an indication that maximum returns can be obtained. This research method is carried out by forming a portfolio based on the IDX BUMN 20 factsheet data, from 10 constituents included in the IDX BUMN 20. Furthermore, the TWR calculation is carried out using the arithmetic average and DWR calculations using the XIRR formulation in ms. excel. The analytical tool used to test the significance of differences in performance calculations is an independent t-test which is run using Minitab 14. The results of this study indicate that portfolio performance using the TWR calculation appears to be higher than the DWR calculation. The TWR calculation ignores the possibility of adding funds to the investment, in contrast to the DWR calculation which calculates the possibility of additional reinvestment. TWR is based on buy and hold assumptions only. Therefore, referring to the test results, it can be suggested that the investment that should be made by investors is to follow the buy and hold mechanism, although this study ignores other factors such as investor preferences in investing, so that it can be a development for further research.